The XLZD Design Book: towards the next-generation liquid xenon observatory for dark matter and neutrino physics - Aalbers, Jelle; Böse, Kai; Chauvin, Antoine; Doerenkamp, Maike; Guida, Matteo; Hammann, Robert; Hansmann-Menzemer, Stephanie; Hötzsch, Luisa; Keller, Michael; Krosigk, Belina von; Lindner, Manfred; Marrodán Undagoitia, Teresa; et al. (The European physical journal. C, Particles and fields, 2025)
This report describes the experimental strategy and technologies for XLZD, the next-generation xenon observatory sensitive to dark matter and neutrino physics. In the baseline design, the detector will have an active liquid xenon target of 60 tonnes, which could be increased to 80 tonnes if the market conditions for xenon are favorable. It is based on the mature liquid xenon time projection chamber technology used in current-generation experiments, LZ and XENONnT. The report discusses the baseline design and opportunities for further optimization of the individual detector components. The experiment envisaged here has the capability to explore parameter space for Weakly Interacting Massive Particle (WIMP) dark matter down to the neutrino fog, with a 3$$σ $$evidence potential for WIMP-nucleon cross sections as low as $$3× 10^{-49}\mathrm \,cm^2$$(at 40 GeV/c$$^2$$WIMP mass). The observatory will also have leading sensitivity to a wide range of alternative dark matter models. It is projected to have a 3$$σ $$observation potential of neutrinoless double beta decay of $$^{136}$$Xe at a half-life of up to $$5.7× 10^{27}$$ years. Additionally, it is sensitive to astrophysical neutrinos from the sun and galactic supernovae.